2009
DOI: 10.1209/0295-5075/88/24002
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon polaritons in photonic superlattices containing a left-handed material

Abstract: We analyze one-dimensional photonic superlattices which alternate layers of air and a left-handed material. We assume Drude-type dispersive responses for the dielectric permittivity and magnetic permeability of the left-handed material. Maxwell's equations and the transfer-matrix technique are used to derive the dispersion relation for the propagation of obliquely incident optical fields. The photonic dispersion indicates that the growth-direction component of the electric (or magnetic) field leads to the prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 35 publications
4
41
0
Order By: Relevance
“…Singh et al further pointed out that such zero-ε and zero-μ gaps can exist in any 1D PCs, not necessarily only in RHM/RHM superlattices, and studied the properties of defect modes in such band gaps [68] . In 2009, Reyes-Gómez et al [69] proposed a different but rather inspiring interpretation for such zero-ε and zero-μ gaps. Noticing that ε = 0( μ = 0) corresponds to (bulk) plasmon polariton (PP) excitation of the dispersive medium (layer 2), the authors argued that such gaps arise from the interactions between propagating modes and bulk PPs.…”
Section: Zero-ε and Zero-μ Gaps And Their Interactions With The Zero-mentioning
confidence: 99%
“…Singh et al further pointed out that such zero-ε and zero-μ gaps can exist in any 1D PCs, not necessarily only in RHM/RHM superlattices, and studied the properties of defect modes in such band gaps [68] . In 2009, Reyes-Gómez et al [69] proposed a different but rather inspiring interpretation for such zero-ε and zero-μ gaps. Noticing that ε = 0( μ = 0) corresponds to (bulk) plasmon polariton (PP) excitation of the dispersive medium (layer 2), the authors argued that such gaps arise from the interactions between propagating modes and bulk PPs.…”
Section: Zero-ε and Zero-μ Gaps And Their Interactions With The Zero-mentioning
confidence: 99%
“…Therefore, the advent of metamaterials has given a new thrust to plasmonic studies due to its potential applications in wave guiding and sensing. Recently, a new type of gap has been reported, in various arrangements of RHM/LHM bilayers, that is, periodic, quasi-periodic, fractal, and disordered superlattices illuminated by obliquely incident electromagnetic wave [13][14][15]. It is shown that the longitudinal electric field component (magnetic) in a TM (TE) configuration, absent at normal incidence, excites longitudinal bulk-like plasmon-polaritons (PPs).…”
mentioning
confidence: 99%
“…We begin by focusing the attention within the frequency region where the linear theory predicts a longitudinal bulk-like PP gap [13,14] and investigate the switching on the transmission properties by increasing the incident power. We choose an incidence angle of θ π∕24 and plot in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work on 1-dimensional (1D) photonic heterostructures formed by alternating a righthanded material (RHM), such as air, with an ideal isotropic left-handed material (LHM) has evidenced the existence of a zero-n (null average of the refractive index) band gap [9][10][11][12][13][14][15] that is insensitive to lattice parameter changes (in contrast to the behavior exhibited by Bragg gaps), and exhibited bulk plasmon polariton modes, whether the stacking arrangement is periodic, quasiperiodic, or even disordered. [16][17][18][19][20][21][22][23] However, in practice, an isotropic LHM is still a great challenge for researchers, as the available LHM structures are intrinsically anisotropic. The reflection from a 1D photonic heterostructure containing an anisotropic LHM has been investigated by Wang and Gao.…”
mentioning
confidence: 99%